Museum of Digital Art utilizing mixed reality for display and interaction - Rodriguez, Kriz Anne Louise C.; Araneta, Maureen Anne L. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
The establishment of a digital art museum using mixed reality in the Philippines will emphasize the role of museums as a place of cultural safety and knowledge, despite a fast and ever-changing cultural landscape. The RAISE Model of curation was primarily used as a guide for the museum’s spatial programming, thus creating a more seamless flow that guides
the users in viewing the digital art displays in the museum. Due to the prolonged quarantine periods during the Covid-19 pandemic, accessing cultural heritage and knowledge became a challenge, which affected the museum sector. Museums across the world have started to cope by means of digitizing exhibits and hosting virtual tours through dedicated websites and
domains. There was also a rise in the consumption of digital media, such as art and entertainment in the previous years. Despite museums opening doors once again, the pandemic's lasting impacts have made it clearer that museums need to assess the development of digital offerings in conjunction with their physical site. The challenge now lies in creating a museum experience that combines the novelty of a physical museum and the accessibility of a digital gallery — a problem that can be solved through the used of mixed reality, specifically augmented and virtual reality, which this comprehensive design project for a Museum of Digital Art located in Clark , Pampanga incorporates.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Art museum -- Designs and plans -- Clark(Pampanga).; Art museums -- Clark (Pampanga).; Augmented reality -- Clark (Pampanga).; Mixed reality -- Clark (Pampanga).; Virtual reality -- Clark (Pampanga).